1990
DOI: 10.1210/jcem-71-5-1259
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Dehydroepiandrosterone to Influence Energy and Protein Metabolism in Humans*

Abstract: It was reported recently that 4 weeks of dehydroepiandrosterone (DHEA) treatment [5.55 mmol/day (1600 mg/day), orally] reduced body fat and increased lean body mass in healthy men. The present study was performed to examine whether these effects could be explained by increased energy expenditure and muscle protein synthesis. Eight healthy men were given placebo and DHEA (1600 mg/day) for 4 weeks each in a double blind cross-over study. DHEA treatment caused a 9-fold increase in mean plasma DHEA sulfate concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
4
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 6 publications
2
36
4
1
Order By: Relevance
“…DHEA was administered to humans and mammals in high doses with only minor adverse effects, and it is devoid of the harmful immunosuppressive effects of GC (37). Its efficacy in the protection from endotoxemic shock as well as in protection from lethal viral infections warrants further investigations on its mechanisms of action, its activities on the immune system, and on the possibility of treating various infections and other pathologic states of the immune system with DHEA.…”
Section: Discussionmentioning
confidence: 99%
“…DHEA was administered to humans and mammals in high doses with only minor adverse effects, and it is devoid of the harmful immunosuppressive effects of GC (37). Its efficacy in the protection from endotoxemic shock as well as in protection from lethal viral infections warrants further investigations on its mechanisms of action, its activities on the immune system, and on the possibility of treating various infections and other pathologic states of the immune system with DHEA.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Nestler et al (6) reported a 31% decrease in underwater weighingmeasured percent body fat after only 4 weeks of DHEA treatment at 1600 mg/day (6). However, these results were not repeated in obese or normal men following similar protocols (136,140). The study by Flynn et al (132) reported a trend for a decrease in body weight, with no changes in body composition after 12 weeks of 100 mg/day oral DHEA in 39 healthy older men (132).…”
Section: Exogenous Dheamentioning
confidence: 97%
“…9 Nevertheless, the relationship of DHEAS and DHEA to lipids and lipoproteins in men is still debated; some studies show either signi®cant inverse correlation 9,10 or no correlation with lipids, particularly triglycerides. 11,12 Studies evaluating the impact of DHEA replacement on lipids and lipoproteins in men have reported either no modi®cation, 13,14 or signi®cant decrease in total and HDL cholesterol 15 or in total and LDL cholesterol. 16 Physical exercise can be effective for controlling diabetes and reducing serum lipid levels and other CHD risk factors.…”
Section: Introductionmentioning
confidence: 99%